The Rett syndrome--clinical presentation of the first 9 Albanian cases - Preza, B; Baboçi, H; Ashta, A; Lleshi, L (Brain & development (Tokyo. 1979), 1990)
Out of the 1,000 patients (girls, 2-18 years old) examined since 1984, there were identified 9 cases with classical symptoms of the Rett Syndrome. Geographically considered the cases were concentrated in three regions. First, in the eastern part of Albania (Korça-Pogradec-Peshkopia) and in the western-central part (Durrës-Tirana), within a distance of 40-45 km in each region. The most important fact is that the two cases in Durrës town lived in the same quarter, at a distance of 300 m. Secondly, in the northern part of the country (Shkodra city), averagely 150 km away from the first centers. Three of the patients became relatively improved both intellectually and physically, due to their parents' special care as well as intensive medical rehabilitation and music therapy.